Association between Bone marrow lesions & synovitis and symptoms in symptomatic knee osteoarthritis. Issue 3 (March 2020) - Perry, T.A.; Parkes, M.J.; Hodgson, R.J.; Felson, D.T.; Arden, N.K.; O'Neill, T.W.
Summary: Objective: Bone marrow lesions (BMLs) on MRI are typically subchondral in location, however, a proportion occur at knee ligament attachments and also include a cyst-like component. Our aim was to determine whether the volume of BML subtypes and synovial tissue volume (STV) was associated with symptoms in symptomatic knee OA. Method: Images were acquired in a sub-sample who had taken part in a randomised trial of vitamin D therapy in knee OA (UK-VIDEO). Contrast-enhanced (CE) MRI was performed annually. In those who had ≥1 follow-up and a baseline scan ( N = 50), STV and BML volume was assessed. BMLs were categorised by location and by the presence/absence of a cyst-like component. WOMAC was assessed annually. We used fixed-effects panel-regression modelling to examine the association between volume and symptoms. Results: There was no association between knee pain and total subchondral BML volume ( b = 0.3 WOMAC units, 95% CI -0.3 to 1.0) or total ligament-based BML volume ( b = 1.9, 95% CI -1.6 to 5.3). The volume of subchondral BMLs with a cyst-like component was not associated with pain ( b = 0.8, 95% CI -0.5 to 2.1) however, the volume of the cyst-like component itself was associated with pain ( b = 51.8, 95% CI 14.2 to 89.3). STV was associated with pain ( b = 2.2, 95% CI 0.6 to 3.7). Conclusion: The volume of the cyst-like component from subchondral BMLs with a cyst-like component was associated with knee pain. BML location, however, did not influence symptoms. STV was also associated with knee symptoms.